INTEGRATION OF ISLAMIC RELIGIOUS EDUCATION VALUES IN PREVENTING CYBERBULLYING IN ADOLESCENT GIRLS: BIBLIOMETRIC ANALYSIS AND LITERATURE STUDY - Syifa Samrotul Fauziah; Mokh. Iman Firmansyah; Nurti Budiyanti (Kafa`ah: Journal of Gender Studies, 2026)
Cyberbullying poses a serious threat to the mental health of adolescent girls in the digital era. However, global literature on cyberbullying prevention is still dominated by psychological and mental health approaches that focus on risk factors, emotional impacts, and individual interventions. The integration of religious values, particularly Islamic Religious Education (PAI), in strengthening adolescent girls' digital literacy remains relatively limited. This study aims to identify gaps in the global literature and demonstrate the relevance of integrating PAI values in preventing cyberbullying among Muslim adolescent girls. The study employed a qualitative approach with an integrative literature review design, analyzing 42 Scopus-indexed articles through exploratory bibliometric analysis using VOSviewer and thematic analysis of PAI, the Qur'an, and Hadith literature. The results show that cyberbullying studies are still dominated by publications from Western countries and the fields of Medicine and Psychology, with a primary focus on risk factors, psychological impacts, and mental health-based interventions. Keyword co-occurrence analysis also indicates that discussions on religious values, spirituality, and preventive character building are still not a primary focus in the conceptual network of the analyzed research. This study identifies three dimensions of Islamic Religious Education (PAI) values relevant for integration into digital literacy: muraqabah as spiritual awareness (aqidah), hifzhul lisan (verbal communication) and the principle of Iqra' as communication ethics and critical literacy (sharia), and noble morals as a manifestation of expected digital behavior. These findings contribute to the development of a preventive framework based on Islamic Religious Education (PAI) values to strengthen the digital literacy of Muslim adolescent girls in the social media era.